Localization of the Endocannabinoid-Degrading Enzyme Fatty Acid Amide Hydrolase in Rat Dorsal Root Ganglion Cells and Its Regulation after Peripheral Nerve Injury - Lever,IJ; Robinson,M; Cibelli,M; Paule,C; Santha,P; Yee,L; Hunt,SP; Cravatt,BF; Elphick,MR; Nagy,I; Rice,ASC (J.Neurosci., 2009)
Fatty acid amide hydrolase (FAAH) is a degradative enzyme for a group of endogenous signaling lipids that includes anandamide (AEA). AEA acts as an endocannabinoid and an endovanilloid by activating cannabinoid and vanilloid type 1 transient receptor potential (TRPV1) receptors, respectively, on dorsal root ganglion (DRG) sensory neurons. Inhibition of FAAH activity increases AEA concentrations in nervous tissue and reduces sensory hypersensitivity in animal pain models. Using immunohistochemistry, Western blotting, and reverse transcription-PCR, we demonstrate the location of the FAAH in adult rat DRG, sciatic nerve, and spinal cord. In naive rats, FAAH immunoreactivity localized to the soma of 32.7 {+/-} 0.8% of neurons in L4 and L5 DRG. These were small-sized (mean soma area, 395.96 {+/-} 5.6 microm2) and predominantly colabeled with peripherin and isolectin B4 markers of unmyelinated C-fiber neurons; 68% colabeled with antibodies to TRPV1 (marker of nociceptive DRG neurons), and <2% colabeled with NF200 (marker of large myelinated neurons). FAAH-IR was also present in small, NF200-negative cultured rat DRG neurons. Incubation of these cultures with the FAAH inhibitor URB597 increased AEA-evoked cobalt uptake in a capsazepine-sensitive manner. After sciatic nerve axotomy, there was a rightward shift in the cell-size distribution of FAAH-immunoreactive (IR) DRG neurons ipsilateral to injury: FAAH immunoreactivity was detected in larger-sized cells that colabeled with NF200. An ipsilateral versus contralateral increase in both the size and proportion of FAAH-IR DRG occurred after spinal nerve transection injury but not after chronic inflammation of the rat hindpaw 2 d after injection of complete Freund's adjuvant. This study reveals the location of FAAH in neural tissue involved in peripheral nociceptive transmission